In silico and in vitro structure-stability-function relationship of analog peptides of Stigmurin and its antibacterial and antibiofilm activities. (July 2022) - Furtado, Allanny Alves; Daniele-Silva, Alessandra; de Oliveira, Igor Rafael Resende; Mendes, Raudiney Frankilin Vasconcelos; Santos, Elizabeth Cristina Gomes dos; Carvalho, Enéas de; Damasceno, Igor Zumba; Parente, Adriana Marina e Silva; Sena, Kêsia Xisto da Fonseca Ribeiro de; Silva-Júnior, Arnóbio Antônio da; Ximenes, Rafael Matos; Vieira, Davi Serradella; et al.
Abstract: Multidrug-resistant bacterial infections are a threat to public health worldwide, which boosts the urgent need for pharmacological research for new drugs. Although the peptides without disulfide bridges from scorpions have shown antimicrobial action, usually their toxicity hamper their pharmacological application. Stigmurin is a non-hemolytic cationic peptide from Tityus stigmurus venom with antibacterial effect and toxicity on normal cells. In this approach, the conformational changes and stability of two Stigmurin analog peptides, named StigA8 and StigA18, were evaluated by circular dichroism, as well as the mechanism of interaction with bacterial membranes in silico . In addition, the in vitro and in vivo antibacterial activity and the action against the biofilm formed by multidrug-resistant Staphylococcus aureus were investigated. StigA8 (+4) and StigA18 (+5) revealed the ability to change their structural conformation depending on the medium composition, and high stability at different temperatures and pH conditions. Both analog peptides showed greater ability to interact with bacterial membranes in silico when compared to the native one. StigA8 and StigA18 demonstrated low hemolytic action, with non-toxic effect on G. mellonella larvae up to 120 mg/kg. StigA8 and StigA18 presented a broad spectrum of antibacterial action in vitro, especially against multidrug-resistant clinical isolates. The analog peptides (7.5 µM) also reduced the biofilm biomass of multidrug-resistant S. aureus, as well as increased the larval survival of the Galleria mellonella infected larvae. Therefore, StigA8 and StigA18 showed a beneficial potential in the treatment of bacterial infections, constituting promising bioactive components for the development of new antimicrobial agents. Graphical Abstract: ga1 Highlights: StigA8 and StigA18 showed high structural stability at different temperature and pH. StigA8 and StigA18 interact with the lipid bilayer of bacteria in silico. StigA8 and StigA18 showed low hemolytic effect in vitro and non-toxic action in vivo. StigA8 and StigA18 showed action against multidrug resistant bacteria in vitro. StigA8 and StigA18 revealed antibiofilm action with antibacterial effect in vivo.